Beta-Catenin Plasma Test: Liver Fibrosis Degree Assessment in Chronic Hepatitis B Patients - Anne Marrya; B. Rina A. Sidharta; Lusi Oka Wardhani; JB. Suparyatmo; MI. Diah Pramudianti (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Liver fibrosis caused by chronic hepatitis B infection leads to significant mortality and morbidity. Monitoring and evaluation of liver fibrosis progression depend on the ability to detect the fibrosis. Liver biopsy as a gold standard for liver fibrosis is an invasive technique, while Fibroscan ® with transient elastography as a non-invasive technique has a limitation. Therefore, a biomarker is needed to detect liver fibrosis. Beta-catenin is a multifunctional protein, which has a Wnt-regulated transcription factor and resides in hepatocytes. Hepatitis B virus infection activates Wnt/beta-catenin and affects the expression of target genes for liver fibrosis. This study aimed to analyze the diagnostic performance of plasma beta-catenin levels using transient elastography as a standard reference to assess the degree of liver fibrosis in patients with chronic hepatitis B infection. This was an observational analytic study with a cross-sectional design. The analysis was performed on 70 chronic Hepatitis B patients between December 2020 and January 2021 at Dr. Moewardi Hospital, Surakarta. This ROC analysis was used to determine the cut-off point. The best AUC point was chosen using a 2x2 diagnostic test table. The cut-off point for plasma beta-catenin was 73.132 pg/mL and AUC was 0.793 (CI 95%: 0.681-0.906; p<0.001), indicating that the results were statistically significant with p<0.05. Sensitivity of 74.3%; specificity of 71.4%; PPV of 72.2%; NPV of 73.5%; LR (+) 2.6; LR (-) 0.36 were obtained. The beta-catenin level was <73.132 pg/mL. A total of 26 subjects were at risk for liver fibrosis with transient elastography >8 kPa. Plasma beta-catenin levels had moderate performance as a liver fibrosis marker.